PENGEMBANGAN PROTOTIPE TROLI OTOMATIS MENGGUNAKAN ARDUINO UNO R3 BERBASIS ANDROID - Wahyuni, Tantri; Rohmanudin, Wildan; Bastian, Ade (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2021)
The presence of robotics technology aims to create an effective and efficient life, making human work easier. Automatic trolley prototype designed to assist shopping activities in a supermarket, designed to provide the best service and for the efficiency of the shopping process itself. Automatic trolley ptototypes are made by integrating software and hardware. Using an android application to run an automatic system, the Bluetooth signal activated by the user can move the automatic trolley that has been installed on the Arduino Uno R3 by utilizing an ultrasonic sensor. Using a DC motor with a maximum speed of 48m / m. The automatic trolley prototype is designed with a scale of 50cm length, 30cm height and 20cm width.